Association between early‐stage diabetic nephropathy and the delayed monophasic glucose peak during oral glucose tolerance test in type 2 diabetes mellitus - Han Zhang; Hanqing Tang; Yunjuan Gu; Zhuqi Tang; Xiaoqin Zhao; Ranran Zhou; Ping Huang; Rongping Zhang; Xinlei Wang (Journal of Diabetes Investigation)
ABSTRACT Aims To explore the relationships between the delayed monophasic glucose peak during oral glucose tolerance test (OGTT) and early‐stage diabetic nephropathy (DN) in patients with type 2 diabetes mellitus(T2DM), and to speculate its potential as a risk factor for early‐stage DN. Materials and Methods This retrospective observational study included 448 participants, all of whom underwent a 3‐h OGTT. Based on peak glucose time, they were categorized into the normal glucose tolerance (NGT) group (n = 76), the early delayed group (n = 98), and the late delayed group (n = 274) for comparison. Furthermore, T2DM patients were subdivided into the non‐DN group (n = 293) and the early‐stage DN group (n = 79) for comparative analysis. Results With the delay in glucose peak time, blood glucose levels increased, insulin secretion function and insulin sensitivity decreased. In logistic regression, ISSI‐2 was independently associated with the delay in glucose peak time in patients with T2DM (OR 0.839; 95% CI 0.776–0.907; P < 0.001). Additionally, 2‐h plasma glucose, OGIS, and AUCC‐peptide0–180 min were independently associated with delayed peak glucose time (all P < 0.001). As glucose peak time was delayed, levels of β2‐microglobulin and UACR increased, and the prevalence of early‐stage DN also increased (all P < 0.050). The delayed monophasic glucose peak was positively associated with early‐stage DN (OR 2.230; 95% CI 1.061–4.687; P = 0.034). Conclusions In patients with T2DM, the delayed monophasic glucose peak during OGTT may be an early predictor of early‐stage diabetes nephropathy, providing early intervention signals for our clinical work.